Challenges of Translating Poetry: The Filipino Translation of William Shakespear's Sonnet 18 - Kay Tepait Juanillo (JETAL: Journal of English Teaching & Applied Linguistic, 2021)
Translation plays an important role in understanding different cultures and societies. Among the various kinds of translation, many scholars have debated the difficulty even impossibility of literary translation, especially Poetry. Translation of poetry requires the preservation of the specific aesthetic and expressive value when the work is transferred from the source language to the target language, which may be changed or altered after translating the work. This study discusses the different linguistic, cultural, and aesthetic issues in translating poetry. This study also discusses the translation issues in the Filipino translation of William Shakespeare’s Sonnet 18. The study shows the complications and sometimes impossibility in translating poetry as compared to other literary works like prose. This study is significant as it encourages experimental strategies that can show the uniqueness of translation as a linguistic and cultural practice.As a result, it can be concluded that the task of the translator is not to express what is to be conveyed but to find the intended effect upon the language into which she/he is translating in a way that leads to produce the echo of the original, even though it is impossible to be able to create a replica of the original text.